Experimental Study on the Influence of Appendages on a Yacht Rolling at Zero Froude Number - Klaka, Kim; Renilson, M. (The Society of Naval Architects and Marine Engineers, 2004)
Yachts tend to roll uncomfortably while at anchor, causing discomfort to the crew and passengers, generating additional stresses on equipment, and making such operations as embarking and disembarking hazardous activities. Currently, there is a dearth of data regarding roll motions at zero forward speed for hull shapes dominated by large appendages. Hence, an experimental study into the effect of large appendages on roll motion was undertaken. The model test results are presented, showing how changes in appendage geometry alter the roll response.